New data on Chilean Urophonius Pocock, 1893 (Scorpiones, Bothriuridae), with description of a new species - Ojanguren Affilastro, Andres Alejandro (2011)
New data are provided on Chilean species of the bothriurid genus Urophonius Pocock, 1893. Urophonius mondacai, n. sp., from central Chile is described. Urophonius tumbensis Cekalovic, 1981, is redescribed according to modern standards, and information about its distribution and ecology provided. Urophonius transandinus Acosta, 1998, is redescribed, its known distribution enlarged, and data on the morphological variation among its populations provided. A modification to Maury's (1973) group division of the genus is presented. Urophonius is divided into two groups instead of three as proposed by Acosta (1988). A distribution map for the three species covered in this contribution is provided, together with a key to the Chilean species of the genus.